INCREASED WORK PRODUCTIVITY THROUGH STRENGTHENING VISIONARY LEADERSHIP OF THE ORGANIZATIONAL CLIMATE AND CREATIVITY (Empirical Studies using Correlational Methods and SITOREM Analysis in State Junior High School Teachers in Depok City) - Briliantina Indrati, Prof. Dr. H. Thamrin Abdullah. Mm., Mpd, Dr. Rita Retnowati, M.S (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
This study aims to find strategies and ways to increase teacher work productivity by examining the strength of the relationship between work productivity and visionary leadership, organizational climate and creativity. The study uses a sequential explanatory design, using correlational statistical methods and SITOREM analysis to determine priorities and recommendations for indicators that need to be improved. A total of 252 civil servant teachers at the Depok City State Junior High School. The results of the quantitative research found that all variables had a significant positive relationship, individually showing a strong while together very strong with work productivity, the next analysis was the analysis of Scientific Identification Theory to Conduct Operation Research in Education Management (SITOREM), with the stages of identification the strength of the influence between the research variables, and based on the weight of each indicator that comes from the independent variable that has the largest contribution, then the priority order of the indicators that need to be improved and those that need to be maintained isarranged.